Analisis Model Atas Faktor Penentu Nilai Perusahaan (Studi Pada Perusahaan Pulp and Paper yang Terdaftar di BEI 2015-2019) - William Fernando; Temy Setiawan (Akuntabilitas, 2021)
This study aims to analyze the factors that influence firm value, where the independent variables consist of ownership structure, capital structure and gender diversity, and financial performance as a mediation. The research used is Pulp & Paper companies listed on the Indonesia Stock Exchange for the period 2015 – 2019. Using samples from 7 manufacturing companies. By using a sample of 7 manufacturing companies. The test analysis used is the SmartPLS 3.0 program. Based on the results of the study, ownership structure and gender diversity have no significant effect on firm value, capital structure and financial performance have a significant positive effect on firm value, and financial performance has no significant effect on mediating ownership structure and capital structure on the firm. The limitation of this study is to use financial reports sourced from the Indonesia Stock Exchange (IDX) for the pulp and paper sector from 2015-2019 and have financial reports for 5 consecutive years. The implications of this research are expected to provide information for investors on things that can affect the value of the company, especially the paper industry sector.How to Cite:Fernando, W., & Setiawan, T. (2021). Analisis Model Atas Faktor Penentu Nilai Perusahan (Studi Pada Perusahaan Pulp and Paper yang Terdaftar di BEI 2015-2019). Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 231-242.